Modelling and analysis of a retentate-permeate recycle gas permeator - Choong, Thomas S.Y.; Abdul Aziz, Ramlan; Idrees, M; Saidi, Hamdani (1995)
This paper have modelled a retentate-permeate recycle permeator and study has been done on CO2-CH4 binary mixture system. Results showed that retentate-permeate recycle is effective for obtaining a high purity of less permeable component. The detail experimental work and results are available in full text article.